Vamos al Matiné - Hernández, Gabriela (2013)
Going to the cinema -or to a ‘theatre’- in the city of Limon, was a whole ritual in the fifties and sixties, with dressings, special food and beverages for the occasion and after that, the romance in the park. Ali Baba and the Forty thieves, The Monster of the Black Lake, King Kong, The Naughty Boys of Spain and Daniel Santos made their presence at the white screens and the stages of the cinemas and nowadays form part of the mythology of Limon. More than the film, the public was the spectacle: the whole room celebrated the fights and the heroic deeds of the stars at the screen with exclamations while peeling and eating peanuts. At the end of the show, the room was a space covered with peanut shells. Those who experienced these moments deplore the lack of spaces of entertainment and exchange for the younger people...